Jaringan Hotspot Menggunakan Dua Radius MikroTik dan Ethernet Over Internet Protocol Tunnel - Taufik Rahman (INFORMATICS FOR EDUCATORS AND PROFESSIONAL : Journal of Informatics, 2018)
Internet connection with wireless network is very vulnerable in terms of security, even if you already use a password. Therefore more security systems are needed, where only legal users can connect to the wireless network. Legal users are registered on the database with a unique id and password. Unique is different, sensitive information is used. In this study, it aims to create a hotspot with two radius-servers at BSI headquarters operated simultaneously on campus microphones and how to connect BSI campus with headquarters. With user and password on two radiuses ie radius-bsi and radius-parrot, split user domain on campus microtik and EoIP tunnel as its vpn network, student, staff and lecturer can login hostspot. Users who successfully login into the active user hotspot on MikroTik RB1000 Campus and Session User Radius Server MikorTik user Manager at BSI headquarters. Thus hotspot users can be monitored and hotspot user management with two server radios can operate simultaneously on one MikroTik on Campus.